Assessment of independent clinical predictors of early readmission after percutaneous endoluminal left atrial appendage closure with the Watchman device using National Readmission Database. (15th November 2021) - Rahman, Mustafeez Ur; Amritphale, Amod; Kumar, Sagar; Trice, Celeste; Awan, Ghulam Mustafa; Omar, Bassam A.
Abstract: Background: Percutaneous endoluminal left atrial appendage closure (pLAAC) procedure has been used to prevent strokes in patients who are not eligible for long-term prophylactic anticoagulation. Since its approval, multiple studies have looked at its efficacy with comparable outcomes to anticoagulation, the current standard of care. Objectives: To assess the readmission rate and determine the factors associated with readmission after the endocardial pLAAC procedure using the Watchman device. Methods: Data was obtained from the National Readmission Database (NRD), and we used SPSS software to determine statistically significant clinical predictors affecting readmission after implantation of the Watchman device at 30 days. Results: The rate of readmission was found to be 9.2%. The true median cost of index hospitalization for the total population in the study was found to be [median (interquartile range = IQR), p ] USD 24594 (USD 18883–31, 041), whereas the true median cost of admission for those who were getting readmitted after 30 days was [median (IQR)] USD 7699 (USD 4955–14, 243). Multivariate analysis of all clinically relevant predictors showed adjusted ratio for [adjusted odds ratio (OR), 95% confidence interval (95% CI), p -value] female genders (1.288, 1.104–1.503, p = 0.001), discharge to home health care (6.155, 1.509–25.096, p = 0.01), chronic kidney disease (CKD) (1.847, 1.511–2.258, p < 0.001), chronic lung disease (1.419, 1.194–1.686, p < 0.001), heart failure (1.280, 1.040–1.574, p = 0.02), pericardial disorders (1.485, 1.011–2.179, p = 0.04), fluid and electrolyte disorders (1.456, 1.050–2.018, p = 0.02) in those who were getting readmitted at 30-days compared to those who were not readmitted. The median length of stay for the index hospitalization was found to be one day, whereas the median length of stay at the 30-day readmission was reported to be [Median (IQR)] 4 days (2–6 days). Major cardiac reasons for readmission were heart failure, arrhythmias, and pericardial disorders. Conclusion: Our study aims to assess 30-day outcomes in the US population after pLAAC using a Watchman device. Our analysis showed that one in ten patients were getting readmitted. In addition, chronic kidney disease, chronic obstructive pulmonary disease, heart failure, and pericardial disorders were associated with higher readmission rates. These findings will help us assess clinical correlations and predict which patients are more at risk of readmission after a Watchman procedure. Highlights: This study uses NRD to assesses the outcomes after percutaneous left atrial appendage closure within 30 days. Our analysis found that almost one in every ten patients was getting readmitted after the procedure within 30 days. Chronic Kidney disease and Heart failure were associated with a higher rate of readmission after the procedure. Gastrointestinal Bleeding was one of the primary causes for readmission; however, it was not associated with an increased readmission rate after the procedure. Heart Failure, Cardiac Dysrhythmias, and infections were other significant causes of readmission after the procedure.